AIED Integration in Higher Education: Navigating Impacts on Student Behavior: A scoping review - Shofiah, Nurul; Putera, Zulmy Faqihuddin; Wafa, Iqbal Ali (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
today's digital era, affecting many sectors of life, including education. While AI has great potential to enhance the learning process, especially in developing critical thinking skills in higher education, its use also presents complex challenges. The purpose of this presentation is to examine the integration of AI literacy and critical thinking skills in higher education curricula. The study is based on a systematic review of the existing literature, using the PRISMA (Preferred Reporting Items for Systematic Reviews) model to identify and evaluate relevant research. The results of the review show that although AI can assist in analyzing and evaluating complex information, its effectiveness in improving critical thinking skills is not always consistent and can be affected by various factors, including over-reliance on AI and a lack of in-depth understanding of this technology by educators. In addition, this research highlights the importance of the teacher's role in guiding students to develop a critical attitude towards information generated by AI. In many cases, the critical thinking skills developed through the use of AI depend on how these technologies are integrated and used pedagogically. Barriers such as AI's limitations in understanding emotional nuances and subjectivity, as well as the gap between theory and practice in the use of AI in the classroom, were also identified as key challenges. Thus, this study not only highlights the potential benefits of AI in education but also warns about the risks and challenges that must be carefully managed. The findings provide profound insights for educators and policymakers in designing relevant and futuristic curricula, which not only prepares students for future technological challenges but also ensures that they retain strong critical thinking skills.